Transforming public health with artificial intelligence: an applied case study - Guimarães, Camille; Araújo, Andressa Clara; Pimentel, Cristiane (Brazilian Journal of Production Engineering, 2026)
Digital transformation in healthcare has driven process automation, resource optimization, and personalized patient care. This study aimed to implement and evaluate the use of free Artificial Intelligence (AI) tools applied to the pharmacy, outpatient clinic, continuing education, and Patient Safety Center (PSC) sectors in a public hospital. The methodology consisted of an exploratory and descriptive study, based on an initial evaluation of 30 AI tools using a Likert scale decision matrix to select the five most suitable solutions. After technical training, the implementation revealed a significant increase in the familiarity and engagement of professionals with 4.0 technologies. Tools such as You.com in the pharmacy and Synthesia in continuing education showed high acceptance, optimizing the speed of regulatory searches and the effectiveness of internal training. The study concludes by demonstrating that digital innovation is viable and accessible even in resource-limited scenarios.